Dynamic Performance Detection of CFRP Composite Pipes based on Quasi-Distributed Optical Fiber Sensing Techniques - Wang, Hua-Ping; Feng, Si-Yuan; Gong, Xiang-Shu; Guo, Yan-Xin; Xiang, Ping; Fang, Yu; Li, Qi-Ming (Frontiers in Materials, 2021)
For the high strength, good corrosion resistance and stability, carbon fiber reinforced polymer (CFRP) composites have been made into pipes to transfer gasses and oils in subsea environment. The structural performance of CFRP composite pipes is particularly important to sustain the regular operation of the delivery system. To obtain the in-field behavior of the CFRP composite pipes, quasi-distributed optical fiber sensing techniques are developed based on the multiple configuration of fiber Bragg grating (FBG) sensing elements. Theoretical investigation on dynamic performance of the pipes is performed. Experiments on cantilever CFRP pipes with surface-attached FBGs in series and packaged FBG sensors have been conducted to check the feasibility and effectiveness of the proposed sensing technique. Results validate the good measurement performance of the proposed sensors and the accuracy of the vibration analysis. The study can be adopted to instruct the establishment of the structural health monitoring system of CFRP composite pipes and assess the safety operation state of the pipe systems.